2007
DOI: 10.1016/j.electacta.2006.11.019
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanisms of corrosion inhibition of AA2024-T3 by vanadates using the split cell technique

Abstract: The mechanisms of corrosion inhibition of AA2024-T3 by vanadates were studied in this work using the split cell technique and polarization curves. The electrochemical behavior of clear solutions containing metavanadates and orange solutions containing decavanadates was clearly distinctive. Injection of metavanadates to the cathode side of the different split cell setups greatly reduced the galvanic current, indicating a potent inhibition of the oxygen reduction kinetics. The galvanic current never exhibited a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 47 publications
0
67
1
Order By: Relevance
“…[8][9][10][11][12] For AA2024-T3, inhibition has been reported to be pH and concentration dependent (speciation dependent) and has been strongly linked to tetrahedrally coordinated vanadates reducing cathodic oxygen reduction kinetics on Cu-containing intermetallic compounds (IMCs) through a surface adsorption mechanism. [11][12][13][14] Other works have shown that vanadates also provide inhibition to Zn-rich Al alloys such as AA7075. 15,16 This, in combination with evidence of vanadate inhibition on Zn-based materials, [5][6][7] has led to speculation that vanadates likely interact with the Zn-rich phases in 7xxx series Al alloys (possibly in addition to the Cu-rich features).…”
mentioning
confidence: 99%
“…[8][9][10][11][12] For AA2024-T3, inhibition has been reported to be pH and concentration dependent (speciation dependent) and has been strongly linked to tetrahedrally coordinated vanadates reducing cathodic oxygen reduction kinetics on Cu-containing intermetallic compounds (IMCs) through a surface adsorption mechanism. [11][12][13][14] Other works have shown that vanadates also provide inhibition to Zn-rich Al alloys such as AA7075. 15,16 This, in combination with evidence of vanadate inhibition on Zn-based materials, [5][6][7] has led to speculation that vanadates likely interact with the Zn-rich phases in 7xxx series Al alloys (possibly in addition to the Cu-rich features).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In particular, vanadates in NaCl solutions have been shown, under specific conditions, to be modest anodic inhibitors and potent cathodic inhibitors for 2024. [3][4][5][6][7][8] Furthermore, there are ways to functionalize soluble vanadates through the formation of films and conversion coatings, and by incorporation into organic coatings.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In particular, vanadates in NaCl solutions have been shown, under specific conditions, to be modest anodic inhibitors and potent cathodic inhibitors for 2024. [3][4][5][6][7][8] Furthermore, there are ways to functionalize soluble vanadates through the formation of films and conversion coatings, and by incorporation into organic coatings. [7][8][9][10][11][12] Additionally, a number of vanadate surface treatments and pigmented organic coatings applied to zinc and aluminum substrates have been observed to "self-heal" in a fashion resembling that shown by chromate-based coatings.…”
mentioning
confidence: 99%
“…The V-Ce(III) and V-Zn processes provided protection similar to that of sealed SAA films (Figure 12(c,b)), while the V-Ni process provided protection similar to that of CAA-sealed films ( Figure 12(a)). It is noteworthy that the levels of corrosion protection provided by the double dip processes are achieved without the requirement for sealing of the films, and also that the corrosion tests were carried out for much longer than the times often employed for neutral salt spray testing of sealed panels treated by CAA and SAA, usually about 300-336 h. 19,20 The protection provided by the double-dip processes is considered to be due to corrosion inhibition provided by vanadate ions that suppress the cathodic reaction [12][13][14] and increase the pitting potential. 15 The low solubility of heavy metal vanadates assists the retention of vanadates in the unsealed pores.…”
Section: Salt Spray Testingmentioning
confidence: 99%
“…13 It has been reported that inhibition does not involve reduction of vanadate. 14 Inhibition was observed mainly in alkaline conditions when tetrahedrally coordinated vanadate, metavanadate and pyrovanadate were present and the pitting potential was increased. 15 An increased pitting potential and suppressed dissolution of S phase was reported for a range of copper-containing intermetallic particles with vanadate addition to alkaline sodium chloride solutions.…”
Section: Introductionmentioning
confidence: 99%